A new endemic representative of the genus Rascioduvalius S. B. Ćurčić, Brajković, Mitić & B. P. M. Ćurčić from Mt. Zlatibor, Western Serbia (Trechini, Carabidae, Coleoptera) - Ćurčić Srećko B. (Archives of Biological Sciences, 2005)
A new species of cavernicolous and endemic trechine ground beetles Rascioduvalis zlatiborensis n. sp., is described and diagnosed in the present paper. Also, all important taxonomic features are considered and illustrated. The type specimens of the new species were collected from the Markova (= Ršumska) Pećina Cave, village of Gornji Ljubiš, Mt. Zlatibor, Western Serbia. The new species and its congeners belong to a separate phyletic lineage of Tertiary age. All members of Rascioduvalius S. B. Ćurčić, Brajković, Mitić & B. P. M. Ćurčić are distributed in Western Serbia only, where they have gone through intense differentiation and radiation due to evolution of the karstic relief.